2021
DOI: 10.1186/s12887-021-02956-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the factors associated with tongue pressure between children with class I and Class II malocclusions

Abstract: Background The relationship between tongue pressure and masticatory performance during the mixed dentition period in cases of Class II malocclusion has not been clarified. The aim of this study was to determine differences in tongue pressure-related factors, including maxillofacial morphology and masticatory performance, between Class I and Class II malocclusions during the mixed dentition period. Methods A total of 56 children with Class I maloccl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Partal and Aksu (12) measured tongue and lip pressure of children with Class II dental malocclusion and did not find a difference between them and those with Class I dental malocclusion. On the other side, other authors (13,15) found an association between tongue pressure and maxillofacial morphology in children and suggest a relationship between tongue position and its force.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Partal and Aksu (12) measured tongue and lip pressure of children with Class II dental malocclusion and did not find a difference between them and those with Class I dental malocclusion. On the other side, other authors (13,15) found an association between tongue pressure and maxillofacial morphology in children and suggest a relationship between tongue position and its force.…”
Section: Introductionmentioning
confidence: 91%
“…Researches were carried out to establish normative values for orofacial strength and endurance and to investigate the possibility of influences of age (4) , sex (6) , and clinical conditions such as mouth-breathing (7) , obstructive sleep apnea (8) , and temporomandibular disorders (9) . However, few studies have been conducted on the influence of malocclusion on the force or pressure exerted by the tongue and lips (10)(11)(12)(13)(14)(15)(16) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation